The Effect of Questioning Technique and Critical Thinking on Students Reading Comprehension - Henny, Indria; Azhary Tambusai; Ahmad Laut Hasibuan (International Journal of Educational Research Excellence (IJERE), 2022)
The purpose of this study is to determine whether questioning technique and critical thinking can help improve reading comprehension ability in students enrolled in XII Grade Mathematics and XII Grade Science. The study used a quasi-experimental design in which a control group was pre-tested and a post-test group was tested. This study looks at the students of State Senior High School 13 Medan. The research sample used to determine the results of the experiment was chosen from among the students in the class, with a random selection being made from each group. The data analysis used in this study is an indication of the intelligence of the participants. The Mann-Whitney test is used as a method for testing hypotheses. The study found that questioning techniques and critical thinking help improve students’ reading comprehension skills. The effectiveness of students' critical thinking skills is higher in the experimental class who use the effective questioning technique in Unit XII MIA 1 than in the control class in Unit XII MIS 1.